2015
DOI: 10.1177/1365480214566280
|View full text |Cite
|
Sign up to set email alerts
|

The causes and effects of English teachers’ turnover: A case from Afghanistan

Abstract: One of the challenging issues that educational organizations in developing countries face in staffing classrooms with qualified teachers is the high rate of teachers' turnover. It creates problems for schools, which eventually leads to substandard instruction and low student achievement. This research explores the causes of English teachers' turnover in a Non-Government Educational Organization in Kabul, Afghanistan. The results indicate that lack of teachers' motivation, low salary, communication gap between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 29 publications
0
21
0
Order By: Relevance
“…Marks and Printy, 2003) and developing countries (e.g. Khawary and Ali, 2015;Nguni et al, 2006;Tesfaw, 2014) have already found evidence for the direct relationship between transformational leadership and several teachers' job attitudes. This supports the argument that transformational leadership is important across various societies and as such should receive attention.…”
Section: Limitations and Suggestions For Further Researchmentioning
confidence: 97%
See 2 more Smart Citations
“…Marks and Printy, 2003) and developing countries (e.g. Khawary and Ali, 2015;Nguni et al, 2006;Tesfaw, 2014) have already found evidence for the direct relationship between transformational leadership and several teachers' job attitudes. This supports the argument that transformational leadership is important across various societies and as such should receive attention.…”
Section: Limitations and Suggestions For Further Researchmentioning
confidence: 97%
“…In the case of developing countries, the collection of data concerning teacher attrition is often poor and not always reliable (Mulkeen and Crowe-Taft, 2010 in their review of the literature on Sub-Saharan Africa). The available data indicate that in developing countries, there is a teacher retention problem to some extent (Khawary and Ali, 2015;Mulkeen and Crowe-Taft, 2010;Rinke, 2008) and that, as in other countries around the world, this attrition is concentrated in teachers' first years in the profession (Mulkeen and Crowe-Taft, 2010). In general, the early attrition rates have led to several consequences such as teacher shortages (Ingersoll, 2001) and deteriorating student performance (Ronfeldt et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, those teachers who were not satisfied, due to some factors, as a lack of career advancement opportunities, low motivation, low salary, or ineffective communication with leaders, were more likely to leave the school. Such high rates of teacher turnover led to less successful outcomes with regard to school effectiveness as well as issues with students, such as emotional instability and poor learning behaviour (Khawary & Ali, 2015).…”
Section: Teachers' Job Satisfaction and School Effectivenessmentioning
confidence: 99%
“…In summary, transformational leadership helped to establish a conventional bond between teachers and the management team. Such a connection led to a firm commitment with a shared vision and purpose for school reform for higher achievement (Khawary & Ali, 2015). In other words, transformational leadership helps to build trust and respect in an inclusive relationship that effectively facilitates the organizational improvements needed for student success.…”
Section: Transformational Leadership For Student Achievementmentioning
confidence: 99%